Superalloys 718 Metallurgy and Applications (1989) 1989
DOI: 10.7449/1989/superalloys_1989_673_683
|View full text |Cite
|
Sign up to set email alerts
|

Welding of Inconel Alloy 718: A Historical Overview

Abstract: The introduction of Inconel alloy 718 represented a major advancement in the nickel-basesuperalloy class of materials. One of the most significant reasons was its lack of sensitivity to strain-age cracking during heat treatment of weldments. In addition, the general weldability of the alloy proved to be quite good. It has reasonably good resistance to fusion-zone cracking, and its sensitivity to heat-affected-zone microfissures in the base metal is comparable to other nickelchromium/nickel-chromium-iron alloys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 6 publications
0
37
0
Order By: Relevance
“…It is interesting to note that microfissures in HAZ were not observed in the present investigation. Previous investigations have shown that HAZ microfissuring tendency is enhance by: welding in aged condition; coarse-grain size; presence of Laves, NbC, ␦-phases at grain boundaries in excessive amounts; higher amounts of boron in the base material; sharp sectional variations in weld shape, as in nail-head shaped welds; welding conditions which promote high solidification stresses [1][2][3][4]. In the present study, welding was carried out in 980 • C solution treated condition.…”
Section: Microstructuresmentioning
confidence: 98%
See 2 more Smart Citations
“…It is interesting to note that microfissures in HAZ were not observed in the present investigation. Previous investigations have shown that HAZ microfissuring tendency is enhance by: welding in aged condition; coarse-grain size; presence of Laves, NbC, ␦-phases at grain boundaries in excessive amounts; higher amounts of boron in the base material; sharp sectional variations in weld shape, as in nail-head shaped welds; welding conditions which promote high solidification stresses [1][2][3][4]. In the present study, welding was carried out in 980 • C solution treated condition.…”
Section: Microstructuresmentioning
confidence: 98%
“…Ni 3 Nb) [1]. The alloy exhibits reasonably good resistance to weld solidification cracking, but it is prone to microfissuring in heat-affected zone (HAZ) [1][2][3][4]. Another concern is segregation of Nb and consequent formation of Nb-rich Laves phase, a brittle intermetallic compound represented as (Ni, Cr, Fe) 2 (Nb, Mo, Ti), in the interdendritic regions during weld metal solidification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusion welding techniques are used in the joining of superalloys. The weldability of these alloys is generally considered to be good, mostly because of their resistant to strain age cracking due to the sluggish precipitation kinetics of g 00 phase [3]. But, it has been reported that some problems, such as Boron/Niobium segregation, Laves phase and microfissures (liquation cracking), which could occur in either fusion zone or heat affected zone (HAZ) of alloy 718 welds [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, excessive PWHT temperatures may result in increasing amounts and sizes of NbC-type carbides in the parent phase. 14 PWHT specimens of the Inconel X-750, which was aged at 705°C for 2 h, show discontinuities of Cr 23 C 6 in the austenite grain boundary of the HAZ, as shown in Figure 7(a). Figure 7(b) shows an HAZ with continuous instances of Cr 23 C 6 at the grain boundary in the g phase matrix.…”
Section: Microstructure Analysismentioning
confidence: 99%